The Effect of Hostility Reduction on Autonomic Control of the Heart and Vasculature: A Randomized Controlled Trial. Issue 4 (May 2016) - Hajjari, Parisa; Mattsson, Sara; McIntyre, Kathleen M.; McKinley, Paula S.; Shapiro, Peter A.; Gorenstein, Ethan E.; Tager, Felice A.; Choi, Chien-Wen J.; Lee, Seonjoo; Sloan, Richard P.
ABSTRACT: Objective: Hostility is associated with coronary artery disease. One candidate mechanism may be autonomic nervous system (ANS) dysregulation. In this study, we report the effect of cognitive behavioral treatment on ANS regulation. Methods: Participants were 158 healthy young adults, high in hostility measured by the Cook-Medley Hostility and Spielberger Trait Anger scales. Participants were also interviewed using the Interpersonal Hostility Assessment Technique. They were randomized to a 12-week cognitive behavioral treatment program for reducing hostility or a wait-list control group. The outcome measures were preejection period, low-frequency blood pressure variability, and high-frequency heart rate variability measured at rest and in response to and recovery from cognitive and orthostatic challenge. Linear-mixed models were used to examine group by session and group by session by period interactions while controlling for sex and age. Contrasts of differential group and session effects were used to examine reactivity and recovery from challenge. Results: After Bonferroni correction, two-way and three-way interactions failed to achieve significance for preejection period, low-frequency blood pressure variability, or high-frequency heart rate variability ( p > .002), indicating that hostility reduction treatment failed to influence ANS indices. Conclusions: Reduction in anger and hostility failed to alter ANS activity at rest or in response to or recovery from challenge. These findings raise questions about whether autonomic dysregulation represents a pathophysiological link between hostility and heart disease.